Twisted tethered tolanes: unanticipated long-lived phosphorescence at 77 K - Menning, Sebastian; Krämer, Maximilian; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (Journal of the American Chemical Society, 2013)
Influencing the communication within a conjugated system as diphenylacetylene is a challenging subject in molecular electronics. Some examples of twisted tolanes are known, where high twists have been achieved in the solid state by steric encumbrance. The insertion of a spacer system is an alternative way to tailor rotation. Only a few examples of such tethered tolanes exist, and they all suffer from small twist angles (<35°). We report on tolanophanes containing a malonyl tether, where twist angles of almost 80° were reached. Long-lived phosphorescence (4 s at 77 K) was recorded, and quantum-chemical calculations were performed to confirm the experimental results.